Mechanisms Underlying the Rules for Associative Plasticity at Adult Human Neocortical Synapses - Verhoog, Matthijs B. (J Neurosci, 2013)
The neocortex in our brain stores long-term memories by changing the strength of connections between neurons. To date, the rules and mechanisms that govern activity-induced synaptic changes at human cortical synapses are poorly understood and have not been studied directly at a cellular level. Here, we made whole-cell recordings of human pyramidal neurons in slices of brain tissue resected during neurosurgery to investigate spike timing-dependent synaptic plasticity in the adult human neocortex. We find that human cortical synapses can undergo bidirectional modifications in strength throughout adulthood. Both long-term potentiation and long-term depression of synapses was dependent on postsynaptic NMDA receptors. Interestingly, we find that human cortical synapses can associate presynaptic and postsynaptic events in a wide temporal window, and that rules for synaptic plasticity in human neocortex are reversed compared with what is generally found in the rodent brain. We show this is caused by dendritic L-type voltage-gated Ca(2+) channels that are prominently activated during action potential firing. Activation of these channels determines whether human synapses strengthen or weaken. These findings provide a synaptic basis for the timing rules observed in human sensory and motor plasticity in vivo, and offer insights into the physiological role of L-type voltage-gated Ca(2+) channels in the human brain.